Problems and Countermeasures of Chinese Stock Market (CSM) - Feng, Ruiqi (Transactions on Economics, Business and Management Research, 2024)
With the continuous transformation and upgrading of China’s economy, the reform and development of the stock market (SM) is particularly important to the whole country. Therefore, it is a practical significance to study the problems and countermeasures of the China stock market. This study sorts out the main problems in the CSM and discusses the root causes and influence of these problems. The study found that the main problems in CSM include excessive policy intervention, an immature stock market, and the number of listed companies. Based on these findings, the research proposes to appropriately reduce policy intervention, upgrade the quality of CSM, and control the number of list companies (LCs). This study provides valuable references for policymakers to help them develop more scientific and reasonable SM measures. The research also provides specific suggestions for the market participants to improve the market behavior, which helps to accelerate the healthy development of the market.